Sn substitution endows NaTi2(PO4)3/C with remarkable sodium storage performances. Issue 9 (15th June 2020) - Zheng, Weiguo; Wu, Min; Yang, Chen; Tang, Zhiguo; Hu, Haining
Abstract: The further development of clean energy requires the use of more stable and reliable energy storage system. In addition to lithium ion battery power supplies, sodium ion batteries also have prospects for application and development thanks to the low cost and abundant resource. NaTi2 (PO4 )3 has attracted much attention due to its three-dimensional channels for sodium ion transfer. In order to meliorate sodium storage properties of NaTi2 (PO4 )3 electrode, a facile strategy of Sn substitution at Ti sites was employed, and a series of electrodes were successfully synthesized through sol-gel route. The electrochemical performances of Sn substituted composites are significantly improved compared with bare NaTi2 (PO4 )3 /C. And it was found that NaSn0.2 Ti1.8 (PO4 )3 (NTP/C-Sn-2) delivers the largest capacity, and it also demonstrates the outstanding cycling performances. NTP/C-Sn-2 has discharge capacity of 131.1 mAh g −1 at 4 A g −1 in rate test and 121.4 mAh g −1 at 1 A g −1 after 1000 cycles in cycling test. The experimental results show that NaTi2 (PO4 )3 /C with Sn substitution with proper content exhibits the great potential in anode for sodium ion batteries, and can further provide reference for next generation electrode materials and battery systems.